(untitled) (Polish Yearbook of International Law, 2016)
Despite the universal condemnation of torture, the prevention of appalling practices of ill-treatment has not been achieved in the 21st century. The repugnant practice persists and even increases because of the disingenuous interpretations of the definition of torture and the lack of effective enforcement mechanisms. Notwithstanding the cogency of the absolute and non-derogable prohibition of torture, particularly regarding the treatment of detainees, nowadays corporal punishment as a punitive measure is arguably a recurring phenomenon in several former British colonies and in States where the legal system is based on Islamic Sharia. While several legally binding universal and regional instruments prohibit torture in general terms, with no specific definition, the scope of the Convention against Torture definition was narrowed down by the lawful sanctions clause. The universality of the definition has been undermined by the inclusion of this clause, since different States have different practices when it comes to lawful and unlawful sanctions. The intractable problem of the interpretation of the definition by the State-Parties and the lack of effective control mechanisms has perennially posed the greatest challenge with respect to compliance with International Human Rights Law. In light of the above, this article seeks to critically dissect the lawful sanctions clause within the context of corporal punishment.